Peningkatan Nilai Dissolved Oksigen dan Penetralan pH pada Air Laut Menggunakan Destilasi Sederhana - Idayani Sangadjisowohy (Poltekkes Kemenkes Padang, 2023)
The issue of water pollution in big cities in Indonesia has shown very concerning signs. This study aims to determine the value of Dissolved Oxygen and pH before and after treatment using distillation. The method is simple experimental design with post test only group control design, carried out in the chemistry laboratory of the Ternate Polytechnic, with sample of 10 liters sea water. The researchers used simple distillation system consisting of electric stove, hose and container filled with cold water. Dissolved Oxygen in seawater samples before treatment did not meet the requirements for class 3 water which based on Government Regulation RI No 22 of 2021 must exceed 3 ppm while the test results showed that Dissolved Oxygen was only 1.7 ppm. dissolved oxygen in seawater samples with distillation treatment has met the requirements for class 3 water which must exceed 3 ppm while the test results show that DO is 6.7 ppm. pH in seawater is still in the category that meets the requirements. pH in seawater after distillation has changed from alkaline to neutral with a test number of 7. In conclusion, distillation is able to increase Dissolved Oxygen and neutralize pH. The recommendation for further research to carry out sampling at several points in order to obtain broader water characteristics, so that it can be used as a reference for decision making at the local government.